A Política de Turismo no estado de Goiás: um estudo sobre as escalas institucionais de intervenção - Carvalho, Gisélia Lima (2015)
One of the characteristics of the development of tourism, not only in Brazil, is its close relation to public and governmental actions, as well as the expectation surrounding its effects on local tourist territories. In view of this, the present thesis attempts to understand the historical process which promoted the tourism policy in Goiás State – by establishing a link between federal, state, and municipal scales of intervention –, in addition to assessing the effects on income and formal employment in local tourist territories. As claimed by governmental discourses, tourist activities are expected to produce their own dynamics, leading to clear results in the economy of cities. Therefore, this thesis proposes a time- and space-oriented theory concerning the State's role as a crucial actor in the tourism policy over the last four decades. This study included bibliographical research in the fields of public policies, tourism policy, and State planning; inventory and analysis of official documents on tourism; survey of quantitative data regarding municipal employment and income; fieldwork. The conclusions reached by this thesis claim the existence of an embryo State policy for tourism that can be traced back to the 1960s; also, despite the current overrated nature of spontaneity of tourism development in Goiás, the historical analysis reveals that the federal State is the leading character. On the other hand, social and economic impacts sought by public investments do not materialise in the expected quantities and quality within the municipal scale, as is usually the case in the execution of public policies. Hence local actors need to show a more effective shared responsibility within tourism planning.